SharePoint Framework for Developers: 2 Authoring and Debugging Solutions. - Malik, Sahil (linkedin.com, 2018)
Learn to build and debug SharePoint Framework (SPx) web parts and extensions, and deploy your solutions using Office 365 and third-party CDNs.